Intelligent Packaging in the Food Sector: A Brief Overview - Patricia Müller; Markus Schmid (Foods, 2019)
The trend towards sustainability, improved product safety, and high-quality standards are important in all areas of life sciences. In order to satisfy these requirements, intelligent packaging is used in the food sector. These systems can monitor permanently the quality status of a product and share the information with the customer. In this way, food waste can be reduced and customer satisfaction can be optimized. Depending on the product, different types of intelligent packaging technologies are used and discussed in this review. The three main groups are: data carriers, indicators, and sensors. At this time, they are not that widespread, but their potential is already known. In which areas intelligent packaging should be implemented, how the systems work, and which values they offer are dealt in this review.